Plasmonic layer-selective all-optical switching of magnetization with nanometer resolution - D. O. Ignatyeva (Nature Portfolio, 2019)
The density of magnetic storage media is limited by the superparamagnetic limit when scaling down magnetic bits. Here, the authors open the way for stacked magnetic storage by using all-optical switching and addressing different magnetic layers by polarization-dependent excitation of plasmon-polaritons.